Pengaruh Koordinasi Mata-Tangan terhadap Keberhasilan Pukulan Forehand dan Backhand pada Pemain Tenis Lapangan - Alfaroh Devid B Maharaja; Ali sahbana Nasution; Nanda Trisia Sinaga; Endiko Sadewa Ginting; Nurkadri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Hand-eye coordination is a person's ability to align visual function with hand motor movements to achieve precision in directing an object to the desired target. In tennis, this ability is a crucial factor in determining a player's success in hitting shots, particularly in basic techniques such as the forehand and backhand. This study aims to analyze the influence of hand-eye coordination on the effectiveness of forehand and backhand shots in tennis players. The study used a quantitative approach with a correlational design involving 30 adolescent tennis players from a tennis club in Medan City. Data were collected through a hand-eye coordination test (ruler drop test) and a shot skills test that assessed ball direction accuracy. These findings emphasize the importance of coordination training in tennis training programs, particularly in the basic technique phase.